2010
DOI: 10.1103/physreve.82.050301
|View full text |Cite
|
Sign up to set email alerts
|

Towards a relevant set of state variables to describe static granular packings

Abstract: We analyze, experimentally and numerically, the steady states, obtained by tapping, of a two-dimensional granular layer. Contrary to the usual assumption, we show that the reversible ͑steady state branch͒ of the density-acceleration curve is nonmonotonous. Accordingly, steady states with the same mean volume can be reached by tapping the system with very different intensities. Simulations of dissipative frictional disks show that equal volume steady states have different values of the force moment tensor. Addi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
85
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(102 citation statements)
references
References 22 publications
16
85
1
Order By: Relevance
“…The sharp drop of φ is associated to a discontinuous order-disorder transition previously reported for this model [18] and also observed in granular dynamics of polygonal grains [27]. The appearance of the minimum packing fraction as a function of tap intensity has been reported for several models (including a frustrated lattice gas model [28], a Monte Carlo type deposition [21] and a realistic discrete element method simulation [21]) and in experiments of tapping with a quasi-2D system [29,30]. For the model we use in this paper, the minimum φ has been shown to exist even if bidisperse systems are considered [31].…”
Section: Initial Packingsmentioning
confidence: 84%
See 1 more Smart Citation
“…The sharp drop of φ is associated to a discontinuous order-disorder transition previously reported for this model [18] and also observed in granular dynamics of polygonal grains [27]. The appearance of the minimum packing fraction as a function of tap intensity has been reported for several models (including a frustrated lattice gas model [28], a Monte Carlo type deposition [21] and a realistic discrete element method simulation [21]) and in experiments of tapping with a quasi-2D system [29,30]. For the model we use in this paper, the minimum φ has been shown to exist even if bidisperse systems are considered [31].…”
Section: Initial Packingsmentioning
confidence: 84%
“…This has been pointed out in Refs. [29,30] where steady states with the same φ but bearing different stresses were obtained through tapping. In our simulations, forces are not calculated and therefore the stress tensor cannot be obtained.…”
Section: Effect Of Packing Fractionmentioning
confidence: 99%
“…Stationary states of static granular packs subjected to pulsed excitations have been considered by a number of workers [1][2][3][4][5][6][7][8][9][10][11][12][13]. In recent years, the granular community has been focused on finding the correct variables to describe the macroscopic stationary states of static granular packs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has also been widely studied experimentally [32][33][34][35][36] and by means of simulations [28,37,38]. In [28,38] it was shown that the packing fraction φ of the bed is not a monotonous function of the tapping intensity . This raises the question of whether states with the same density are equivalent or not, in the sense of the statistical mechanical theory.…”
Section: Introductionmentioning
confidence: 99%
“…This question was addressed in [27] where the topology of 2D granular samples in mechanical equilibrium, in the sense of Edwards' theory, was studied. It was already known [28] that samples with the same density and number of particles may not be in the same state of equilibrium since the average force moment tensor can be different. In [27] it was shown that the topology of the contact network (without information on the forces) was enough to distinguish these mechanically different states.…”
Section: Introductionmentioning
confidence: 99%